(untitled) (Novos Olhares, 2013)
This article examines the possibility of building a cultural identity through music in contemporary documentary representation of a Brazilian. From the interviews and testimonies exposed the documentary LAPA (2007), establishes the paradigms of music in relation to its potential as a factor of social inclusion. Furthermore, with the proposed basis of the documentary, evidence of the relationship of music as an important instrument towards cultural activity and ethnography of Lapa, located in the State of Rio de Janeiro.